3D scanning system for smart factory application - Lim, Nigel Zhi Wei (Nanyang Technological University, 2022)
There has been an increasing trend in the utilization of Visual Data. This is due to its ability to overcome limitation of the naked human eyes. Thus, with the increase in interests to utilize Visual Data , it caused an increase in research project which involves the extraction of visual data from images.